Os standards probatórios no âmbito do direito processual civil brasileiro - Lim, Angelo Martin (2024)
The object of this study is the analysis of standards of proof, which are theoretical statements aimed at establishing the degree of confirmation that a factual hypothesis must reach to be considered sufficiently proven in judicial proceedings. The standards of evidence serve three essential functions: i) to establish indispensable criteria for the justification of evidentiary decisions regarding the sufficiency of the evidence produced; ii) to serve as a guarantee for the parties by providing predictability concerning the adequacy of the evidence they need to present; and iii) primarily to promote the allocation of the risks of error between the parties, depending on the socio-political interests at stake. Common law legal systems have long utilized such models to assess evidentiary sufficiency for rational decision-making on factual matters. Although reconciling legal institutions originating from common law with the legal system of civil law tradition countries, such as Brazil, is challenging, this study seeks to demonstrate that the principles supporting the use of standards of proof in foreign legal contexts are equally applicable to the Brazilian legal framework. The methodology adopted is qualitative, based on doctrinal and jurisprudential analysis. To this end, the research includes a review of works by both national and foreign authors, as well as landmark judicial decisions on the subject. Furthermore, a comparative method will be utilized to examine the application of standards of proof in the Brazilian and U.S. legal systems, highlighting their influences and possible adaptations